2009
DOI: 10.3325/cmj.2009.50.567
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Practices of Obtaining Informed Consent for Medical Procedures among Specialist Physicians: Questionnaire Study in 6 Croatian Hospitals

Abstract: Aim To assess physicians' knowledge and practices for obtaining patients' informed consent to medical procedures.Methods An anonymous and voluntary survey of knowledge and practices for obtaining informed consent was conducted among 470 physicians (63% response rate) working in 6 hospitals: 93 specialists in anesthesiology, 166 in internal medicine, and 211 in surgery.Results Only 54% physicians were acquainted with the fact that the procedure for obtaining consent was regulated by the law. Internists and surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 20 publications
5
23
1
3
Order By: Relevance
“…As many as 95% of correct answers were noted when the respondents were asked the question on the necessity of obtaining the patient's consent to undergo higher-risk diagnostic procedures. The results are better than those obtained by Jukic et al [14]. They claim, only 38% of the doctors demonstrated a comprehensive knowledge on the method of obtaining a consent from patients.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…As many as 95% of correct answers were noted when the respondents were asked the question on the necessity of obtaining the patient's consent to undergo higher-risk diagnostic procedures. The results are better than those obtained by Jukic et al [14]. They claim, only 38% of the doctors demonstrated a comprehensive knowledge on the method of obtaining a consent from patients.…”
Section: Discussioncontrasting
confidence: 53%
“…Other authors claim that patients expect to be informed on po tential complications not more rarely than in 1/1000 cases (Newton-Howes [18], and Jamjoom [19] to training. In their study on doctors from Croatia they proved that only 38% had a comprehensive knowledge of issues connected with obtaining a consent to be provided with medical services [14]. Peters, mentioned before, states that only 51% of doctors from New Zealand had ever participated in any training on the necessity to ex press a consent by patients [13].…”
Section: Discussionmentioning
confidence: 99%
“…Our study identified considerable deficiencies in the current knowledge and attitudes of our doctors toward this very crucial area of doctor-patient communication. Surprisingly certain studies from institutions in the western countries such as the USA, Europe, Netherlands and New Zealand have also reported a lack of doctors' knowledge regarding the process of SIC (1,3,(7)(8)(9)(10). Less than ideal level of working knowledge and attitudes regarding SIC on part of our doctors indicates a case for their focused education regarding SIC.…”
Section: Discussionmentioning
confidence: 96%
“…The aim was to cover all fundamental aspects of the knowledge and relevant attitudes that surround the process of SIC and hence generate a representative data that could serve as a valid outcome variable. The questionnaire was prepared by consulting previously used and validated questionnaires employed by other researchers (3,(5)(6)(7)(8).…”
Section: Study Questionnairementioning
confidence: 99%
“…Research in other countries has shown that despite the legal coercion to obtain an informed consent in an appropriate way, what actually happens cannot fulfill legal and professional requirements and the content of most of them did not meet accepted standards. It seems that systematic education of medical staff is needed to improve the process of obtaining informed consent (1,8). Taking a signature on the bottom of an informed consent form is not enough to say that this important part of medical ethics is applied in the hospital.…”
Section: Introductionmentioning
confidence: 99%